Teologi Kontekstual-Transformatif I Wayan Mastra dalam Pengembangan Gereja Kristen Protestan di Bali (GKPB) dari 1970-an sampai 1990-an - Sukamto, Amos (Reformed Center for Religion and Society, 2025)
This study examines the transformative-contextual theology model developed by I Wayan Mastra in revitalizing the Protestant Christian Church in Bali between the 1970s and 1990s. Using historical methods, transforming contextual theology into praxis necessitates the leaders' presence, who are grounded and reflective within their context. They are characterized by three qualities: first, existential sensitivity to the social context in which they operate, as defined in Paulo Freire's concept of conscientization; second, a willingness to be shaped through “candidate training”—both in academic and non-academic spheres—which produces innovative, open, critical, and practical individuals; and third, an inner drive rooted in compassion (splagcnizomai) that motivates leaders to act concretely amid crisis. The Mastra’s methodological framework demonstrates a systematic and visionary approach. Starting from the root causes’ identification, a transformative vision emerges: (1) the core values’ formulation as a catalyst for social transformation; (2) theological renewal through hermeneutical decolonization; and (3) holistic praxis that addresses spiritual, cultural, educational, and economic dimensions. Implementing these practices includes contextualizing the Gospel, strengthening human resources through vocational and formal education, and empowering the congregation economically based on local potential. Thus, this theological model is reflective and operational in striving for human integrity and community liberation.